Implementasi Word Puzzle untuk Mengembangkan Kemampuan Berbahasa - Nurul Mahruzah Yulia; Fitri Hidayati lestari; Ulfa Nurfitri Aprilia; Neyha Fadlilatul A’inia; Linda Ayu Sahara (STIKes Ibnu Sina Ajibarang, 2025)
Language skills are important skills that must be possessed by students of Madrasah Ibtidaiyah (MI) to support the learning process and daily life. However, in practice, there are still many students who have difficulty in developing language skills, such as in vocabulary, reading, and writing. One solution that can be applied is the use of interesting learning media, such as word puzzles. This study aims to examine how the implementation of word puzzle media can improve students' language skills at MI. The method used in this study is a literature review, by examining various sources and previous research results related to the use of word puzzles in language learning. The results of the study show that word puzzles can help increase interest in learning, enrich vocabulary, and train students' reading and writing skills in a fun way. In addition, word puzzles also encourage students to think critically and actively in the learning process. Thus, the use of word puzzles as a language learning medium at MI is highly recommended to improve students' language skills effectively.